Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24031834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arylazo Sulfones on DNA: Binding, Cleavage, Photocleavage, Molecular Docking Studies and Interaction with A375 Melanoma and Non-Cancer Cells

Abstract: A set of arylazo sulfones, known to undergo N–S bond cleavage upon light exposure, has been synthesized, and their activity in the dark and upon irradiation towards DNA has been investigated. Their interaction with calf-thymus DNA has been examined, and the significant affinity observed (most probably due to DNA intercalation) was analyzed by means of molecular docking “in silico” calculations that pointed out polar contacts, mainly via the sulfonyl moiety. Incubation with plasmid pBluescript KS II revealed DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…The experimental results clearly indicated that the synthesized arylazo sulfones can be used as phototoxic pharmaceuticals for cancer treatment (Scheme 40). 68…”
Section: Miscellaneousmentioning
confidence: 99%
“…The experimental results clearly indicated that the synthesized arylazo sulfones can be used as phototoxic pharmaceuticals for cancer treatment (Scheme 40). 68…”
Section: Miscellaneousmentioning
confidence: 99%
“…[14][15][16] In addition, iminopyrazole, pyrimidoquinoline derivatives, and pyridopyrazolpyrimidines are significant molecules that have gained a considerable amount of attention due to their wide variety of industrial and biomedical applications, including antitumor, [17,18] antibacterial, [19,20] antioxidant, [19] antifungal, [20,21] antimalarial, [22] anti-inflammatory, [23,24] antiviral, [18] and an azo derivative that is effective in DNA cleaving. [25] Additionally, imines have been discovered to have cytotoxic and antiproliferative activity against some cancer cell lines, including (Panc-1), (Caco-2), and leukemia, [26,27] in which the azomethine link was thought to be vital for biological activity. [28,29] Herein, we introduce an efficient method for synthesizing an azo-and anil-linked with 3-aminopyrazolo [3,4-b]pyridine derivatives and tested their cytotoxic activity against the A2780CP, MCF-7, and HepG-2 cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles consider the creation of phototoxic compounds and methods of photodynamic cancer therapy. Mikra et al [3] synthesized a set of arylazo sulfones, known to undergo N-S bond cleavage upon exposure to light, and investigated their activity in the dark and upon the irradiation of DNA. It turned out that exposure to UV light leads to structural rearrangements in some arylazo sulfones, increasing their cytotoxic activity against several cell lines.…”
mentioning
confidence: 99%